Determinants of Chlamydia, Gonorrhea, and Coinfection in Heterosexual Adolescents Attending the National Public Sexually Transmitted Infection Clinic in Singapore. Issue 8 (August 2015) - Lim, Raymond Boon Tar; Wong, Mee Lian; Cook, Alex Richard; Brun, Cyrille; Chan, Roy K.W.; Sen, Priya; Chio, Martin
<x xml:space="preserve">Abstract</x> Background Amidst recent trends in rising rates of chlamydia and gonorrhea among Singaporean adolescents, there are limited data on risk factors associated with these infections that may inform prevention strategies in this population. Methods A cross-sectional study of chlamydia and gonorrhea positivity was conducted among 1458 sexually active heterosexual adolescents between 14 and 19 years old attending the national public sexually transmitted infection clinic from 2006 to 2013. The association with demographic and behavioral characteristics was assessed by crude prevalence ratio, and negative binomial regression modeling was used to obtain adjusted prevalence ratios (aPRs). Results Chlamydia positivity was found in 23.6% of males and 36.6% of females, gonorrhea positivity in 33.1% of males and 15.9% of adolescent girl, and coinfection positivity in 10.2% of males and 10.1% of females. In multivariable analysis, chlamydia was positively associated with being Malay (aPR, 1.6; 95% confidence interval [CI], 1.1–2.1) and inconsistent condom use for vaginal sex (aPR, 6.5; 95% CI = 2.4–17.4) in males and with being Malay (aPR, 1.9; 95% CI = 1.5–2.4), inconsistent condom use for vaginal sex (aPR, 2.0; 95% CI = 1.1–3.9), and number of lifetime partners in females (aPR, 1.1; 95% CI = 1.0–1.1). Gonorrhea was positively associated with being Malay (aPR, 3.2; 95% CI = 2.4–4.4), inconsistent condom use for vaginal sex (aPR, 5.4; 95% CI = 2.1–14.4), and number of lifetime partners (aPR, 1.1; 95% CI = 1.0–1.1) in males and with being Malay (aPR, 3.7; 95% CI = 2.4–5.7) in females. Malays had a higher proportion of sexual risk behaviors compared with the non-Malays. Conclusions Ethnicity and high-risk sexual behaviors are important determinants of chlamydia, gonorrhea, and coinfection for adolescents attending this clinic. Targeted interventions are needed to lower the prevalence of high-risk sexual behaviors for the Malay adolescents in this clinic.